Oxygen Isotope Profiles in Adjacent Cores from Mizuho Station, East Antarctica - Kato, Kikuo; Watanabe, Okitsugu (1981)
P(論文) Oxygen isotopic composition (δ^<18>O) in the cores from the Antarctic and Greenland ice sheets provides important information about paleoclimatic records. However, the interpretation of the δ^<18>O values in the cores is not always easy. Mizuho Station is under the influence of a stationary katabatic wind. Periods of erosion, deposition and neither occur on the snow surface around Mizuho Station. Therefore, the interpretation of δ^<18>O values in the cores from the station are more complicated. In the present study was discussed how to obtain information about paleoclimatic records from δ^<18>O in the cores. δ^<18>O values of thick and fine-grained layers with little-developed depth hoar were considered to provide the best information about paleo-temperature records, taking into consideration the following factors : 1) Snow does not always accumulate in every season. 2) A glazed surface is occasionally exposed over one year, resulting in an interruption in the annual layer (s). Subsequent movement of water vapor in firn occurs during depth hoar formation under a large temperature gradient. 3) The variation in annual air temperature is best shown by the air temperature in winter. The profile of δ^<18>O of such layers of one core agrees well with the profile of δ^<18>O of the long depth interval of another core, which is considered to provide information about the trend of variation of mean air temperature in the long term. departmental bulletin paper